Análise de interações professor-aluno com ênfase na afetividade em aulas de física no contexto da educação básica - Araújo, Michely Santos (2012)
This dissertation is a study about affection in the classroom, in the school context, in a school of the federal teaching network in Sergipe, involving a subject like physics. When done, there was a concern for obtaining the viewpoints of both the professor of the discipline and his students about the interactions that involved them, particularly affective interactions. Information acquisition was accomplished in a second year classroom of a high school located in Grande Aracaju, of specific characteristics. The research tools included observation and recording of the developing classes, to apply a questionnaire on teacher interaction and interviews made to both teacher and six students chosen according to their scores in the discipline physics. The approach on affection in the views of Henri Wallon, Lev Vygotsky, Daniel Goleman and Howard Garner, among the main read authors, was adopted here for the analyses of data obtained. Based on this study, postural categories of proximity, responsiveness, attention, physical contact and facial expression related to the processes of teacher-student interaction were identified. Furthermore, the answers given to the questionnaire showed that teachers and students had a similar view on the profile of the teacher. This profile presents a major affective component that explains what was observed in classroom and corroborates what was expressed by each interviewed participant. The study, its methodology and forms of analysis, can help schools and teachers to improve their teaching duties.